All-polysaccharide, self-healing, pH-sensitive, in situ-forming hydrogel of carboxymethyl chitosan and aldehyde-functionalized hydroxyethyl cellulose - Quadrado, Rafael F.N.; Zhai, Zhenghao; Zavadinack, Matheus; Klassen, Giseli; Iacomini, Marcello; Edgar, Kevin J.; Fajardo, André R. (Carbohydrate polymers, 2024)
In situ forming hydrogels are promising for biomedical applications, especially in drug delivery. The precursor solution can be injected at the target site, where it undergoes a sol-gel transition to afford a hydrogel. In this sense, the most significant characteristic of these hydrogels is fast gelation behavior after injection. This study describes an all-polysaccharide, rapidly in situ-forming hydrogel composed of carboxymethyl chitosan (CMCHT) and hydroxyethyl cellulose functionalized with aldehyde groups (HEC-Ald). The HEC-Ald was synthesized through acetal functionalization, followed by acid deprotection. This innovative approach avoids cleavage of pyran rings, as is inherent in the periodate oxidation approach, which is the most common method currently employed for adding aldehyde groups to polysaccharides. The resulting hydrogel exhibited fast stress relaxation, self-healing properties, and pH sensitivity, which allowed it to control the release of an encapsulated model drug in response to the medium pH. Based on the collected data, the HEC-Ald/CMCHT hydrogels show promise as pH-sensitive drug carriers. [Display omitted]